Language Styles in Hisyam Algakh’s At-Ta’syirah: A Pragmatic Stylistic Approach - Hardiyanti, Silvira; Zaini, Hisyam (LISANIA: Journal of Arabic Education and Literature, 2025)
This paper examines the stylistic devices in Hisyam Algakh's poem At-Ta’syirah from a pragmatic stylistic perspective, emphasizing its profound aesthetic and communicative richness. The study aims to identify and analyze these devices and understand the deeper meanings conveyed. At-Ta’syirah's exquisite language and intricate figurative expressions make it a compelling subject, offering unique insights into the poet's artistic genius. Employing a qualitative method with a stylistic analysis approach, the study focuses on identifying majaz, Jinas, Istifham, and ta’kid. Results show At-Ta’syirah contains 12 majaz, 6 Jinas, 7 Istifham, and 1 ta’kid. Analysis reveals majaz conveys profound connotative meanings, Jinas adds beauty and rhythm, Istifham intensifies rhetorical questions, and ta’kid emphasizes main ideas with persuasive force. These devices not only enrich the poem's meaning but also invite readers to contemplate deeper messages, showcasing its exceptional literary merit. From a pragmatic stylistic view, their use serves a profound pragmatic function, demonstrating the intrinsic link between linguistic form, aesthetic appeal, and conveyed meaning. This research underscores At-Ta’syirah's unique importance as a stylistically brilliant work, contributing valuable insights to Arabic poetry and pragmatic stylistics.